Towards 2D layered hybrid perovskites with enhanced functionality: introducing charge-transfer complexes via self-assembly. Issue 17 (8th February 2019) - Van Gompel, Wouter T. M.; Herckens, Roald; Van Hecke, Kristof; Ruttens, Bart; D'Haen, Jan; Lutsen, Laurence; Vanderzande, Dirk
Abstract : This study broadens the family of 2D layered perovskites by the self-assembly of organic charge-transfer complexes in their organic layer. Abstract : This study broadens the family of 2D layered perovskites by demonstrating that it is possible to self-assemble organic charge-transfer complexes in their organic layer. Organic charge-transfer complexes, formed by combining charge-donating and charge-accepting molecules, are a diverse class of materials that can possess exceptional optical and electronic properties.